Integration of Character Education Values in Children's Animated Films: A Critical Analysis of the Development of Visual Technology - Veggy Andika Pratama (Journal Informatic, Education and Management (JIEM), 2026)
The rapid advancement of animation visual technology creates a gap between technical sophistication and depth of character content. Immersive technologies like CGI have the potential to render moral messages superficial and merely visual tack, eclipsed by the demands of spectacular effects and the commercial interests of the industry. This research was conducted by applying a qualitative approach through the library research method. This study adopted a qualitative content analysis approach combined with critical discourse analysis. The results show that: 1). Animation technology has evolved from mere entertainment to a sophisticated narrative tool for conveying moral messages. CGI and immersive techniques create powerful visual metaphors, transforming abstract concepts into emotional experiences that children can easily grasp. 2). Character values such as role models and empathy are no longer presented dogmatically. Modern animation presents them through dynamic character arcs, using visual symbols (such as changes in color or camera angles) to subtly demonstrate a character's moral development. 3). The animation industry faces a tension between educational goals and commercial demands. Market pressures can lead to a dilution of values, where moral messages become shallow and generic to sell franchises and merchandise, hindering narrative depth. 4). The effectiveness of animation in shaping behavior depends on children's identification with the characters and adult guidance. While immersive, resolving moral conflicts too quickly risks instilling unrealistic expectations. The best impact is achieved when the viewing is followed by discussion.